The Evolution of the Early Career Gender Wage Gap - Astrid Kunze (Institute for the Study of Labor (IZA), 2002)
In this paper we investigate when the male-female wage differential arises: Does it evolve over the early career or does it exist right from entry into first employment onwards? For the analysis we use new administrative longitudinal data and focus on the early careers of skilled workers in Germany. We adopt a simple human capital theory approach. Advantages of the data for this type of analysis are that we observe complete work and wage histories, and that we observe workers' skills. Regarding entry wages we find a gap of approximately 25 percent. For the early career, i.e. up to eight years of work experience, the differential stays almost constant at this high level. We find that differences in the apprenticeship training occupation explain the main part of this gap and seem to lead to a permanent wage disadvantage throughout the early career.
Keywords: J7; J16; J3; 330; Male-female wage differentials; human capital; early career; sample selection; occupation; apprenticeship training; Lohndifferenzierung; Geschlecht; Berufseinstieg; Schätzung; Facharbeiter; Deutschland